The Gendered Impacts of COVID-19 amid Agrarian Distress: Opportunities for Comprehensive Policy Response in Agrarian South Asia. Issue 4 (December 2020) - Nichols, Carly E.; Jalali, Falak; Ali, Syed Shoaib; Gupta, Divya; Shrestha, Suchita; Fischer, Harry
Abstract: COVID-19 and its associated disease control measures have greatly altered everyday life. The burden of these challenges has fallen disproportionately on women. Drawing on qualitative inquiry in agrarian north India and Nepal, this research note analyzes how South Asian COVID-19 lockdowns have affected women's labor responsibilities in sometimes surprising ways. We find increased responsibilities for caregiving within the household, substantial stress in responding to food insecurity, and growing expectations to fulfill public roles in disease response measures. However, we also find that the return of male migrants and youth has, in some cases, reduced women's farming responsibilities and created opportunities for household togetherness at a time of great uncertainty. We conclude that more research is needed to examine the nuanced aspects of COVID-19's gendered labor impacts to create comprehensive policy responses to address the multiple and sometimes conflicting effects the lockdown has had on agrarian women's informal labor and well-being.